An SI-MISO boost converter with deadbeat-based control for electric vehicle applications - Wang, Benfei (2020)
This paper presents a single-inductor multiple-input single-output (SI-MISO) boost converter with a deadbeat-based control method. The proposed deadbeat-based control has the capability to simultaneously conduct the power regulation from multiple inputs and the output voltage regulation for the SI-MISO boost converter. The advantages of the proposed method are less component count, lower system cost, compatibility for arbitrary number of inputs, fast response, and simplicity for implementation. Hence, the SI-MISO boost converter is a promising interface for the regulation of multiple energy sources as a standalone power system, which can be utilized in electric vehicle applications. To verify the performance of the proposed deadbeat-based control method, a laboratorial prototype of the SI-MISO boost converter is built. The steady-state and dynamic operations are investigated based on the prototype. The experimental results demonstrate that input power and output voltage of the SI-MISO boost converter can be effectively regulated by the proposed control method. The comprehensive comparison with the existing methods is conducted to further illustrate the advantages of the proposed deadbeat-based method.